Fermented Codonopsis pilosula residue improved milk performance of lactating donkeys by enhancing antioxidant capacity and regulating metabolism - Zhou, Miaomiao; Huang, Fei; Du, Xinyi; Liu, Guiqin; Wang, Changfa (Frontiers in Veterinary Science, 2024)
The fermented Codonopsis pilosula residue (FCPR) has a promoting effect on animal health, but it has not been studied in livestock feed. This study investigated the effects of FCPR addition on the milk performance, milk metabolites, and blood biochemical parameters and metabolites of lactating donkeys. Twelve healthy multiparous lactating Dezhou donkeys were randomly divided into two groups (with 6 donkeys in each group): control group (without FCPR, C) and FCPR group (200 g of FCPR per head per day, FF). The experiment lasted for 5 weeks. The milk and blood samples were collected at the end of the experiment. The results showed that addition of FCPR significantly increased the daily milk yield and the milk components (protein, lactose, solids, solids-not-fat, and lactoferrin) yield of lactating donkeys and the weight gain of foals (p < 0.05). A total of 568 metabolites were detected in donkey milk, including 21 differential metabolites between group FF and group C. Compared to group C, the significantly up-regulated metabolic pathway in the FF group was renin secretion (p < 0.05). In addition, the FCPR significantly increased the concentrations of urea, complement C4 (C4), total antioxidant capacity (T-AOC), and catalase (CAT) in the blood, while reducing the concentration of malondialdehyde (MDA) (p < 0.05). A total of 753 metabolites were detected in serum of donkeys, including 86 differential metabolites between group FF and group C. Compared to group C, the significantly up-regulated metabolic pathways in the FF group were renin secretion, cAMP signaling pathway, regulation of lipolysis in adipocytes, and fatty acid biosynthesis (p < 0.05). The above results indicated that FCPR addition enhance the milk performance of lactating donkeys by activating the immune system, increasing the antioxidant capacity, and improving the glucose and lipid metabolism. These results provide a foundation for the development and utilization of FCPR additives, which is beneficial for livestock production and improving animal welfare.